Community integration enhances migrants’ satisfaction with primary care across districts with varying economic levels: survey evidence from Guangzhou, China - Yao Xiao; Sisi Zhong; Lingshan Chen; Lingshan Chen; Diwen Xiao; Wenhao Huang; Shangjian Wu; Luwen Zhang; Luwen Zhang (Frontiers in Public Health)
BackgroundThis study investigated the satisfaction of migrant populations in Guangzhou with primary care and explored how community integration and economic development at the district level influenced this satisfaction. This study aimed to provide empirical evidence and recommendations for improving primary care utilization and community integration among migrant populations.MethodsWe conducted a stratified random sampling of 1,996 migrant individuals from seven districts in Guangzhou. A custom-designed questionnaire was used to collect data on demographic characteristics, satisfaction with primary care, and community integration, including willingness to seek help, neighborhood interactions, and participation in community activities. Multi-variate linear regression analysis was used to identify factors associated with satisfaction with primary care.ResultsThe mean satisfaction score for primary care was 3.29 ± 0.76. Participation in community activities was positively associated with satisfaction, with participants often reporting higher scores (increases of 0.08 and 0.28 points, respectively; p < 0.05). Greater neighborhood interaction and willingness to seek assistance from local authorities also increased satisfaction (0.11 and 0.37 points, respectively; p < 0.05). Residing in districts with moderate or good economic conditions further enhanced satisfaction (0.37 and 0.10 points, respectively; p < 0.05).ConclusionAlthough migrant populations in Guangzhou generally report high satisfaction with primary care, their level of community integration remains limited. Enhancing community public services and fostering a stronger sense of community belonging are promising strategies for improving primary care management and services for migrant populations.